Penetapan Isbat Nikah di Bawah Umur dan Pencatatannya di Kantor Urusan Agama - Suharyono Paputungan; Roy Marthen Moonti; Ibrahim Ahmad (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
The phenomenon of nikah siri and underage marriage in Indonesia reflects complex legal and social challenges. Although Law No. 1/1974 and its revision through Law No. 16/2019 have set the minimum age for marriage at 19 years, the practice remains widespread, particularly in rural areas. Nikah siri, which are not officially recorded, are often performed for economic reasons, ignorance of the law, or social pressure. As a result, couples and children from these marriages face legal uncertainty, such as difficulties in obtaining birth certificates, inheritance rights, and legal protection. This research uses normative legal research methods. Isbat nikah emerged as a solution to legalize unregistered marriages, including for underage couples. However, this mechanism poses a dilemma: on the one hand it provides legal protection for couples and children, but on the other hand it opens a loophole to legitimize child marriages that violate the principles of child protection and gender equality. The role of the Religious Affairs Office (KUA) and Religious Courts is crucial in enforcing the law and preventing abuse of isbat nikah. Through this research, it is recommended that regulations be tightened, communities educated and KUAs strengthened to ensure harmony between formal law and community needs, while still protecting children's rights.